3He along the ultraslow spreading AMOR in the Norwegian-Greenland Seas. (May 2019) - Stensland, Anne; Baumberger, Tamara; Mork, Kjell A.; Lilley, Marvin D.; Thorseth, Ingunn H.; Pedersen, Rolf B.
Abstract: The majority of undiscovered hydrothermal vent fields are thought to be located on slow and ultraslow spreading ridges. Locating new vent sites on these ridges is important due to their tendency to host large seafloor massive sulfide deposits. It is also important as it can increase our understanding of the tectonics at ultraslow spreading ridges as well as giving us an understanding of how hydrothermal venting in these regions affect and interact with the surrounding water column. To assess the hydrothermal productivity of the slow to ultraslow spreading Mohns and Knipovich ridge segments of the Arctic Mid-Ocean Ridge we used the primordial isotope 3 He. Due to the conservative nature of 3 He, this isotope can function as a tracer both for hydrothermal activity and on the ocean current pathways. In addition to assessing the hydrothermal productivity of the ridges we also studied the impact the ridges have on ocean circulation. Between 2006 and 2016, 400 water samples were collected along the Mohns Ridge and the Knipovich Ridge and 117 samples were collected in two transects crossing each ridge. The results show that the surface mixed layer (500–0 m depth) directly above each ridge has higher than equilibrium values of δ 3 He, which we interpret as an effect of the bottom topography on the vertical mixing. We also observe direct indications of at least two undiscovered vent sites along the Mohns Ridge, making the total count of 7 vent fields along this 550 km ridge segment, which gives a vent field frequency (Fs ) of 1.27 sites/100 km. This number is comparable to the vent field frequency on other ultraslow ridges. By comparing the current speed to non-buoyant plume measurements obtained at the previously discovered Loki's Castle and the Jan Mayen vent fields (JMVF) we made an estimate of the 3 He flux at these vent fields. This estimate gave a flux of 0.22 mmol/km/mm/yr from Loki's Castle, which is well below the world's average of 0.33 mmol/km/mm/yr. However, the flux rate estimated here is comparable to estimates previously calculated from the ultraslow Gakkel ridge. The northeastern termination of the Mohns Ridge, where Loki's Castle is located, is also the thinnest part of the ridge segment indicating a low magmatic influence. The flux rate of the JMVF was 0.40 mmol/km/mm/yr and thus higher than the global average. This could indicate an influence from the Jan Mayen hot spot as similar flux rates has been found at other hot spot influenced vent sites. This study not only illuminates the hydrothermal productivity of ultraslow spreading ridges, but also adds a considerable dataset of helium isotopes in Nordic Seas.